Likwidacja Prokuratorii Generalnej Rzeczypospolitej Polskiej w 1951 roku – efekt sowietyzacji systemu prawnego w Polsce Ludowej - Tkaczuk, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The explosion II of the world war made impossible the kelter of the Office of the Attorney of the Republic of Poland. The end of the war permitted the Office of the Attorney of the Republic of Poland to resume the activity. Under the management of the new President of the Office of the Attorney of the Republic of Poland of Jerzy Polamin the office worked to 1951 the year. Communist authorities for new concerning ideas of the political system of the state decided to do away the Office of the Attorney of the Republic of Poland and to charge the protection of the law the property of State to legal advisers working in government-institutions. The aim of this study is to presents key assumptions had communist authorities heading to liquidation of the Office of the Attorney of the Republic of Poland due to the progressive Sovietization of the legal system in People`s Poland. The changes in the state system were so important that they ultimately in the liquidation of the Office of the Attorney of the Republic of Poland and forced legal services for the state`s property interests to be based on principles completely different from the previous ones. The article is based primarily on archival materials subject to analysis and criticism.
Keywords: communism; the property of State; legal representation; legal protection of the public interests; sovietization